Prevalence of Mental Health Issues Among Secondary School Students in Surabaya, Indonesia, Using the Strengths and Difficulties Questionnaire - Nafisah, Ainun; Tharani Balamurugan (Tecno Scientifica Publisher, 2026)
Adolescent mental health is a growing concern worldwide, yet evidence from Indonesia remains limited. This study examined the prevalence of mental health issues among secondary school students in Surabaya using the Strengths and Difficulties Questionnaire (SDQ). A cross-sectional survey was conducted across four schools, involving 167 junior and senior high school students. Participants self-reported emotional symptoms, conduct problems, hyperactivity/inattention, peer relationship difficulties, and prosocial behavior. Data were analyzed using descriptive statistics and non-parametric tests to explore differences across gender, age, school type, and school level. Findings revealed that 24.6% of students were at substantial risk of mental health difficulties. In contrast, 70.7% of students were unlikely to experience clinically significant problems, and only 1.8% were at risk of low prosocial behavior. Female students reported higher total difficulty scores but also demonstrated greater prosocial behavior compared to males. Additionally, students in public schools showed higher levels of prosocial behavior than those in private schools.